Hydro-treating and Hydro-isomerisation of Sunflower Oil using Pt/SAPO-11: Influence of Templates in Ultrasonic Assisted with Hydrothermal Synthesis - Shanmugam Palanisamy; Durona Palanisamy; Mugaishudeen Gul; Kannan Kandasamy; Borje Sten Gevert (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Pt/SAPO-11 mesopores type materials has successfully synthesized using different templates, such as: diethylamine (DEA), dimethylamine (DMA), and n-propylamine (n-PA), under ultrasonication coupled with hydrothermal treatment or independently with hydrothermal treatment. The influences of structure directing agent (SDA) and synthesis method are investigated by different characterization techniques and the role of the material as catalyst in hydrotreating of sunflower oil has examined. The synthesized materials have been characterized by X-ray Diffraction (XRD), Scanning Electron Microscope (SEM), and Fourier Transform Infra Red (FT-IR) techniques. It is found that SAPO-11 material which has synthesized with n-PA as a template has the characteristics of high silicon incorporation. Hydrotreating of sunflower oil is carried out in a fixed bed reactor with Pt impregnated SAPO-11 catalyst and a detailed study on the isomerization is performed by varying the operating parameters like temperature and space velocity. The high selectivity of Pt/SAPO-11 catalyst is achieved by uniform pore size and acidity. Also the pore opening of the catalyst has a major effect in the selectivity of the catalyst. Further, it represents a higher ratio of isomers compared to other synthesized catalysts on hydro-treating of sunflower oil.  Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).